Peran Manajemen Sumber Daya Manusia Rumah Sakit pada Masa Implementasi BPJS Kesehatan untuk Mengurangi Keluhan Pasien - Putu Ratih Pravitasari; I Wayan Septa Wijaya; Ni Putu Indah Rosita (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
The transformation of PT Askes (Persero) into BPJS Kesehatan in 2014 brought significant changes to Indonesia’s health insurance system. This transformation required hospitals to adapt to the new system, particularly in human resource management (HRM). This study employed a literature review method, with articles sourced from Google Scholar within the period of 2015–2025. The primary focus of this research is to examine the role of hospital HRM during the implementation of BPJS Kesehatan in addressing patient complaints. The findings indicate that effective HRM includes performance management, talent development, competency building, work discipline, and the creation of a conducive work environment. These factors significantly influence employee performance and patient satisfaction. Furthermore, structured HR development through education, training, and strategic planning has been proven to improve productivity and employee loyalty. This study underscores the importance of applying good governance principles in hospital HRM to ensure that healthcare services are of higher quality, timely, and patient-centered.